2015
DOI: 10.18805/ijar.5714
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of Ghungroo and Large Black pig at organized institutional farm conditions

Abstract: Present study was conducted to compare the production and reproduction performance of Ghungroo and Large Black breeds maintained at ICAR Research Complex for North Eastern Hill Region, Nagaland Centre, Jharnapani, Nagaland. The birth weight (1.09 vs. 0.96 kg), pre-weaning growth rate (174.90 vs. 141.40 g/day) and matured body weight at 7 months (64.74 kg vs. 53.13 kg) were significantly higher (p<0.05) in Large Black gilts as compared to Ghungroo. However, the age at first estrus (209.70 vs. 244.42 days) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…The adoption of breeding technology is also affected and influence by educational level and age of the farmers (Khanal & Gillespie, 2011), in which the findings of our study confirmed this finding as well. Several studies also confirmed that there are several factors that influence the adoptability of AI breeding technology and most of these factors are the level of education of the farmers, family size, distance to AI station and occupation in agriculture or animal husbandry (Mushonga et al, 2017;Patra et al, 2014). Similarly, the findings of this study also confirmed that educational attainment is positively and significantly influence to the farmers perceptions towards AI such as awareness, acceptability, status and prospects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The adoption of breeding technology is also affected and influence by educational level and age of the farmers (Khanal & Gillespie, 2011), in which the findings of our study confirmed this finding as well. Several studies also confirmed that there are several factors that influence the adoptability of AI breeding technology and most of these factors are the level of education of the farmers, family size, distance to AI station and occupation in agriculture or animal husbandry (Mushonga et al, 2017;Patra et al, 2014). Similarly, the findings of this study also confirmed that educational attainment is positively and significantly influence to the farmers perceptions towards AI such as awareness, acceptability, status and prospects.…”
Section: Discussionsupporting
confidence: 80%
“…A cross-sectional descriptive survey employing a mixed-method design of a qualitative-quantitative methodological triangulation was used to determine the sociodemographic information, and perceptions of farmers about AI in relation to its application in cattle production. The design employed a pragmatic approach through the complementarity of the findings from survey, interviews and focus group discussions to permit the breadth and depth of understanding about the subject matter and enable data collection within a short period (Patra et al, 2014;Ybañez et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the increase of chicks weight at hatch could due to that organic iodine easily transferred to egg and improve the transport and absorption of minerals (Xiao et al,2015) and regulate the metabolism of embryo (Davis et al, 2000). Similar results were reported by Patra et al (2016) who mentioned that the size of egg had a significant effect on chicks ̛ weight at hatch. The observed increase of relative weight of fabricious gland for chicks of organic iodine group compared with those of inorganic iodine might due to that organic iodine transferred easily to egg, then to embryo and take advantage of alternative absorption routes, provides protection towards mineral antagonisms, against indigestible complexes formation and can elevated immunological function compared to inorganic iodine (Saripinar-Aksu et al, 2012).…”
Section: Hatching Traitssupporting
confidence: 90%